2019
DOI: 10.1016/j.envint.2018.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Urinary concentrations of monohydroxylated polycyclic aromatic hydrocarbons in adults from the U.S. Population Assessment of Tobacco and Health (PATH) Study Wave 1 (2013–2014)

Abstract: Background: Polycyclic aromatic hydrocarbons (PAHs) are environmental pollutants formed from incomplete combustion of organic matter; some PAHs are carcinogens. Smoking, diet, and other activities contribute to exposure to PAHs. Exposure data to PAHs among combustible tobacco product users (e.g. cigarette smokers) exist; however, among non-combustible tobacco products users (e.g., e-cigarette users), such data are rather limited. Objectives: We sought to evaluate exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 43 publications
(53 reference statements)
0
22
0
1
Order By: Relevance
“…Compared with never-user controls, e-cigarette users had significantly higher levels of both 3-hydroxyfluorene [27] and 1-hydroxypyrene present in their urine [27,28]. These carcinogens are metabolites of fluorene and pyrene, respectively, and portend an increased risk of bladder cancer [27]. Similarly, both o-toluidine and 2-naphthylamine, which are known to produce bladder cancer in human and animal studies, were found in urine at 2.3-and 1.3-fold higher levels, respectively, than in non-e-cigarette user controls [12].…”
Section: Carcinogen Urinary Biomarkers In E-cigarette Users Linked Tomentioning
confidence: 85%
See 4 more Smart Citations
“…Compared with never-user controls, e-cigarette users had significantly higher levels of both 3-hydroxyfluorene [27] and 1-hydroxypyrene present in their urine [27,28]. These carcinogens are metabolites of fluorene and pyrene, respectively, and portend an increased risk of bladder cancer [27]. Similarly, both o-toluidine and 2-naphthylamine, which are known to produce bladder cancer in human and animal studies, were found in urine at 2.3-and 1.3-fold higher levels, respectively, than in non-e-cigarette user controls [12].…”
Section: Carcinogen Urinary Biomarkers In E-cigarette Users Linked Tomentioning
confidence: 85%
“…Similarly, both o-toluidine and 2-naphthylamine, which are known to produce bladder cancer in human and animal studies, were found in urine at 2.3-and 1.3-fold higher levels, respectively, than in non-e-cigarette user controls [12]. Thus, e-cigarette users can have urinary biomarker concentrations of several carcinogenic compounds, which are linked to bladder cancer, above the background levels that were found in the samples of nonuser controls [1,12,27,28] Very low levels of such carcinogenic compounds are usually found in human urine samples resulting from environmental or endogenous (eg, food) exposure [6,22,44]. These data suggest that although environmental and endogenous sources may contribute to some of the carcinogenic urinary biomarker levels detected, e-cigarette use extends these levels beyond the background levels of environmental exposures.…”
Section: Carcinogen Urinary Biomarkers In E-cigarette Users Linked Tomentioning
confidence: 89%
See 3 more Smart Citations